Delayed detection programming significantly reduces inappropriate ICD therapies in patients with left-ventricular assist devices. (19th May 2022) - Hohmann, S; Heimeshoff, J; Mueller-Leisse, J; Hillmann, H; Eiringhaus, J; Zormpas, C; Koenig, T; Schmitto, J; Bauersachs, J; Veltmann, C; Duncker, D
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Implantation of a left ventricular assist device (LVAD) is an established therapy for end-stage heart failure, either as bridge to transplantation or as destination therapy. Virtually all LVAD patients carry an implantable cardioverter-defibrillator (ICD) for primary or secondary prevention. The risk of ventricular tachyarrhythmias is significant in LVAD patients, but so is the burden of supraventricular tachycardia and the ensuing risk of inappropriate ICD therapies. The present retrospective study sought to quantify the impact of standard ICD programming vs. a ICD programming with long detection delays on the occurrence of inappropriate ICD therapies. Methods and results: We retrospectively identified 337 consecutive patients (292 male, mean age 54.2 ± 12.3 years) who received a continuous-flow LVAD at our institution. Median follow-up duration was 2.3 (IQR 1.3, 3.7) years. Heart failure etiology was ischemic cardiomyopathy in 155 patients (46.0 %) and non-ischemic dilated cardiomyopathy in 150 (44.5 %). Other etiologies accounted for 32 patients (9.4 %). ICDs implanted at the time of LVAD implantation were single chamber devices in 176 patients (52.2 %), dual chamber devices in 45 patients (13.4 %), and CRT-D in 116 patients (34.4 %) A total of 2228 ICD-treated arrhythmia episodes occurred in 153 patients. 2066 (92.6 %) episodes were appropriate interventions for ventricular arrhythmias. 162 (7.3 %) treatments were inappropriate due to supraventricular tachyarrhythmias (n=115; 71.4 %), sinus tachycardia (n=15; 9.3 %) or oversensing (n=21; 12.9%). We retrospectively compared a standard programming (number of intervals for detection [NID] in the slowest therapy zone ≤ 40) and a long delay programming (NID > 40) and investigated the time to the first inappropriate therapy. A total of 285 patients were programmed to NID ≤ 40 at the first ICD interrogation after LVAD implant, 47 were programmed to NID > 40. Therapies were inactive in the remaining 5 patients. Median NID was 30 (IQR 23, 35) in the standard programming group and 60 (IQR 50, 76) in the long delay group, with similar rates for detection (median cycle lengths 340 [IQR 330, 350] ms and 330 [IQR 322, 340] ms for standard and long delay, respectively). Long delay programming was associated with significantly higher freedom from inappropriate therapies during follow-up (Hazard ratio 0.14, p [log rank] 0.027). No significant difference was observed between groups with regard to time to first appropriate therapy. Conclusion: A number of intervals for detection greater than 40 in the slowest therapy zone was associated with a significantly increased freedom from inappropriate therapies in this large retrospective single-center cohort of LVAD patients with an ICD and should be considered as the default ICD programming strategy in this population.